Evaluation Capacities in the States and U.Ts - Planning Commission (Planning Commission, 1995)
The role of Evaluation is crucial and well recognised for influencing policy analysis and formulation of country level and State level programmes. It improves the resource allocations and budgetary process, and the performance of, the investment projects etc. With the start of the Five Year Plans for bringing speedy economic development in India, the 'Evaluation' gained considerable importance. It was felt that the feedback provided by taking up evaluation studies. Major development programmes, particularly relating to rural development and social development would help the planning process to keep the implementation on course.
Programme Evaluation Organisation Planning Commission Govt. of India